Implementation of the 5S and K3 Programs in The Vocational High School Environment: Community Service as an Effort to Increase Learning Safety and Productivity - Muhammad Navis Mirza (Asian Journal of Community Services, 2023)
The application of safety induction should not only be carried out in the industrial environment but starting from the educational environment, especially vocational education that is oriented to the working world, it is necessary to introduce practical OSH in accordance with the development of each field of work. (Noviansyah: 2020). Community service to the students of SMK GANESA Demak is carried out from 22 December 2021 to 23 February 2023 using the training method with the main target being students of SMK GANESA Demak. The output of this community service is publication in scientific journals & students at SMK GANESA Demak get increased knowledge and skills in OSH so that they can be applied in everyday life.